Determining basic health intervals in tortugas resbaladoras (Trachemys scripta emolli) of the Caño Negro Wildlife Refuge, Costa Rica - Fournier-Gutiérrez, Laura (2020)
The objective of this study was to determinate blood parameters and the presence of parasites in a wild population of tortugas deslizantes (Trachemys scripta emolli) during the dry season of 2013 in the Caño Negro Wildlife Refuge in Costa Rica. Individuals were captured from different gaps using nets. Blood samples were taken to determine chemical parameters of blood and hematocrit, as well as morphological values and body conditions. In addition, samples of feces and ectoparasites were collected. The hematocrit CI 95.0% was [14.7091, 18.7356] and no significant difference were found between sexes. The 95% CI for blood chemistry parameters were: AST (U/L) [87.6214, 148.929], CK (U/L) [1439.2, 2487.08], AU (umol/L) [68.22, 90.43 ], GLU (mmol/L) [4.26, 5.47], PHOS [0.46, 0.61], Ca (mmol/L) [1.99, 2.15], PT (g/L) [22.16, 24.44], K (mmol/L ) [3.31, 3.83], and Na (mmol/L) [127.92, 130.93]. A total of 21 fecal samples was obtained, of which 10 were positive for parasites (23.8% Strongyloides, 14.3% Ascaridia, 9.5% Coccidia, and 9.5% Pentastomid). A leech from the Rhynchobdellidae family was the only ectoparasite found (Placobdella sp.). None of the individuals were ill or had abscesses in relation to their morphological attributes.  Based on the results, the handling used does not represent a risk for this reptile population.